Participation Dynamics in Population-Based Longitudinal HIV Surveillance in Rural South Africa - (:unkn) unknown (My University, 2015)
Population-based HIV surveillance is crucial to inform understanding of the HIV pandemic and evaluate HIV interventions, but little is known about longitudinal participation patterns in such settings. We investigated the dynamics of longitudinal participation patterns in a high HIV prevalence surveillance setting in rural South Africa between 2003 and 2012, taking into account demographic dynamics. At any given survey round, 22,708 to 30,495 persons were eligible. Although the yearly participation rates were relatively modest (26% to 46%), cumulative rates increased substantially with multiple recruitment opportunities: 68% of eligible persons participated at least once, 48% at least twice and 31% at least three times after five survey rounds. We identified two types of study fatigue: at the individual level, contact and consent rates decreased with multiple recruitment opportunities and, at the population level, these rates also decreased over calendar time, independently of multiple recruitment opportunities. Using sequence analysis and hierarchical clustering, we identified three broad individual participation profiles: consenters (20%), switchers (43%) and refusers (37%). Men were over represented among refusers, women among consenters, and temporary non-residents among switchers. The specific subgroup of persons who were systemically not contacted or refusers constitutes a challenge for population-based surveillance and interventions.
Keywords: African Research